Roles of Size, Shape, Amount, and Functionalization of Nanoparticles of Titania in Controlling the Tribo-Performance of UHMWPE Composites - Padhan, Meghashree; Paul, Gourab; Bijwe, Jayashree (Frontiers in Materials, 2020)
AThe present research is based on development and performance evaluation of UHMWPE composites with Titania particles in various amounts and two sizes including nano-size. It also included functionalization of nano-particles (NPs) with siloxane group to enhance the adhesion with the matrix, which would help to reduce wear. Thus, the work had objectives such as; to investigate size effect (nano vs micro) and optimise the amount for best performance from the series with varying amounts (0-8 % in case of micro-composites (MCs) and 0-4 % case of nano-composites (NCs)). It was also of interest to examine effect of siloxane-functionalization of NPs (since they performed significantly better than micro-particles (MPs)) on the performance of nano-composites. It was observed that for adhesive and erosive wear modes, both types of particles (MPs and NPs) proved detrimental in spite of enhanced hardness of the composites basically because of irregular shape of particles, which altered wear mechanisms adversely. NPs proved less detrimental while F-NPs (functionalized NPs) proved marginally detrimental. In abrasive wear mode, both proved beneficial, NPs being more effective than MPs and F-NPs proved the best. The studies revealed how shape of particle influence the performance of composites in various wear modes.